([2.2.2]Cryptand-κ(6) O)potassium (η(4)-cyclooctadiene)bis(η(2)-pyrene)cobaltate(1−) pentane hemisolvate - Brennessel, William W. (International Union of Crystallography, 2012)
The cation, anion, and solvent in the title compound, [K(C(18)H(36)N(2)O(6))][Co(C(8)H(12))(C(16)H(10))(2)]·0.5C(5)H(12), are well separated. The pentane solvent molecules are found in channels along [100] and were modeled as disordered over crystallographic inversion centers. Using the mid-points of the coordinated olefins, the angle between the C(py)/C(py)–Co–C(py)/C(py) and the C(cod)/C(cod)–Co–C(cod)/C(cod) planes (py is pyrene and cod is cyclooctadiene) is 67.6 (2)°. Thus, the overall geometry of the coordination sphere around cobalt is best described as distorted tetrahedral.